2013
DOI: 10.7566/jpsjs.82sa.sa005
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Branched and Linear C6-Alkanes in the MIL-47(V) Metal–Organic Framework.

Abstract: The self-diffusion of hexane isomers in MIL-47(V) has been investigated by combining quasi-elastic neutron scattering (QENS) and molecular dynamics (MD) simulations. Experimentally, the diffusivity of n-hexane is found to be larger than the one of 3-methylpentane. MD simulations bring further insight into the microscopic diffusion mechanism in play confirming that diffusion proceeds via a jump sequence, as observed by QENS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…50 In another study, Rives and co-workers also observed from their MD simulations and QENS experiments that the diffusivities of the dibranched hexanes are larger than those of the monobranched ones in MIL-47(V) in the range of 300−500 K and at a low loading of 1 molecule/u.c. 48 Thus, our observations are in line with these data in the literature.…”
Section: ■ Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…50 In another study, Rives and co-workers also observed from their MD simulations and QENS experiments that the diffusivities of the dibranched hexanes are larger than those of the monobranched ones in MIL-47(V) in the range of 300−500 K and at a low loading of 1 molecule/u.c. 48 Thus, our observations are in line with these data in the literature.…”
Section: ■ Introductionsupporting
confidence: 93%
“…are in the range of 1 × 10 −12 (in IYIHUU) to 12 × 10 −9 m 2 /s (in CUVHIL) for nHex, 2.1 × 10 −11 (in IYIHUU) to 4.59 × 10 −9 m 2 /s (in XADCOW) for 2MP, 6.2 × 10 −11 (in IYIHUU) to 6.98 × 10 −9 m 2 /s (in XADCOW) for 3MP, 0.18 × 10 −9 (in BIMDOR) to 6.19 × 10 −9 m 2 /s (in XADCOW) for 23DMB, and 0.28 × 10 −9 (in AMIMEP) to 6.42 × 10 −9 m 2 /s (in XADCOW) for 22DMB at 298 K for the MOFs considered in this study. The diffusivities of the hexane isomers in the MOFs considered here are sufficiently large at an ambient temperature, and the orders of magnitude are in accordance with those reported by other authors in MOFs and zeolites 3,7,15,24,48,49. The order of magnitude of the diffusivities, reported by Mendes and coworkers from their MD simulation and QENS experiments, of nHex, 3MP, and 22DMB in MIL-53(Fe)-(CF 3 ) 2 and MIL-47(V) are in the range of 10 −9 to 10 −11 m 2 /s at a loading of 1…”
supporting
confidence: 91%
“…Due to the presence of the bulky grafted function, the self‐diffusion coefficients extracted from QENS experiments were found ( Figure ) to be two orders of magnitude smaller in comparison with a related structure, the porous vanadium terephthalate MIL‐47(V) existing in a LP form . Indeed, at 370 K, the orientationally averaged self‐diffusivities of n HEX and 3MP are respectively of 4 × 10 −11 and 8 × 10 −11 m 2 s −1 in MIL‐53(Fe) ‐(CF 3 ) 2 , while they are of 6 × 10 −9 and 4 × 10 −9 m 2 s −1 in MIL‐47(V) for the same temperature.…”
Section: Resultsmentioning
confidence: 96%
“…A pore diameter of 3.2 Å has been reported and the confined nature of this pore channel has been already proved to allow a molecular separation of diverse species via a more efficient packing of certain molecules. Molecules of different kinetic diameters and polarities such as CO 2 and H 2 are likely to show significant differences in terms of diffusivity in this ultramicropore. Here, we evaluate the dynamics of H 2 and CO 2 as single components at different concentrations and as a binary mixture, in MIL-140A­(Zr) by a combination of QENS measures and MD simulations that we have been already successfully employed to probe a series of gas/MOF systems. ,,,− …”
Section: Introductionmentioning
confidence: 99%